Oropharyngoesophageal Scintigraphy in a Case of Complex Swallowing Disorders After a Major Oral Surgery. (December 2021) - Maccora, Daria; Parrilla, Claudio; Lanni, Valerio; Galli, Jacopo; Longobardi, Ylenia; Valenza, Venanzio
Abstract : Abstract: A 75-year-old woman had an occasional finding of a left tonsil mass for dysphagia, which resulted a high-grade squamous carcinoma. Therefore, the patient was sent to have a left pharyngectomy. After the pharyngectomy, the patient reported persistent swallowing disorders and nasal reflux. Consequently, she had an oropharyngoesophageal scintigraphy, demonstrating irregular oral and pharyngeal swallowing phases and confirming reflux episodes into the rhinopharynx and into the oropharynx. In line with these findings, the patient was send to rehabilitation; the abnormal functional mechanisms, previously identified by the scintigraphy, allowed to guide the speech therapy, with a progressive clinical improvement.